Nature's Blueprint in Bioinspired Materials for Robotics - Roh, Yeonwook; Lee, Youngseok; Lim, Daseul; Gong, Dohyeon; Hwang, Suhyeon; Kang, Minji; Kim, Dohyung; Cho, Junggwang; Kwon, Gibeom; Kang, Daeshik; Han, Seungyong; Ko, Seung Hwan (Advanced Functional Materials, 2024)
Soft robotics, an emerging field that focuses on the development of robots utilizing soft, flexible, and deformable materials, is revolutionizing traditional robotics (reliant on rigid materials and motors) and broadening its range of applications and potential uses. In addition, by emulating the structure, function, and characteristics of biological systems, bioinspired materials are facilitating significant progress in a diverse array of soft robotic applications. This review offers an overview of bioinspired materials employed in soft robotics, exploring their potential applications, challenges, and future research directions. For an intuitive understanding, soft robots based on the primary abilities required and the habitats (terrestrial, aquatic, aerial) of the animals and plants they mimic are categorized. Furthermore, real-world applications of developed soft robots in everyday human life are presented. The novel category classification and comprehensive analysis presented in this review provide insights into the development of soft robotic systems with the potential to transform various industries and enhance quality of life.
Keywords: Bio-inspired materials; Bioinspired sensors; Compliant designs; Deformable material; Flexible electrodes; Flexible materials; Soft actuators; Soft robot; Soft robotics; Softer materials; bioinspired sensors; compliant design; flexible electrodes; soft actuators; soft material; soft robots